2023
DOI: 10.56782/pps.135
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic, Flavonoid Contents, Antioxidant and Antimicrobial Activities of Hesperis pendula

Abstract: Many natural products are used in complementary medicine. Plants are widely used among these natural products. In this study, it was aimed to determine the total phenolic and flavonoid contents, total antioxidant status and antimicrobial activity of Hesperis pendula DC. In this context, the above-ground parts of the plant were extracted with ethanol and methanol. The total antioxidant level of the plant was determined using Rel Assay Diagnostics kits (Megatıp/Türkiye). The total phenolic content was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…The findings obtained are shown in Table 2. [30][31][32][33][34][35]. Compared to these studies, the TAS value of D. graveolens was determined to be higher than that of H. pendula, A. kurdica, G. aparine and V. odorata, and lower than that of R. scutatus and H. salicifolium.…”
Section: Antioxidant Activitymentioning
confidence: 93%
“…The findings obtained are shown in Table 2. [30][31][32][33][34][35]. Compared to these studies, the TAS value of D. graveolens was determined to be higher than that of H. pendula, A. kurdica, G. aparine and V. odorata, and lower than that of R. scutatus and H. salicifolium.…”
Section: Antioxidant Activitymentioning
confidence: 93%
“…Then measurements were made at a wavelength of 760 nm (Shimadzu UV-1800 spectrophotometer, Japan). The quantification of the mushroom's total phenolic content was conducted by utilizing the calibration curve derived from the gallic acid standard solution, resulting in a measurement of mgGAE/g [18].…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…These bioactive compounds are not nutritional but have high medicinal properties [3,4]. Many studies have shown that plants have different properties such as nutritive, spice, cosmetic, warming [5,6]. In addition, it has been reported that many plant species around the world have different effects such as antimicrobial, anticancer, antiproliferative, antioxidant, DNA protective [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%